Marine Mammal Behavior: A Review of Conservation Implications - Brakes, Philippa; Dall, Sasha R. X. (Frontiers in Marine Science, 2016)
The three orders which comprise the extant marine mammals exhibit a wide range of behaviors, varying social structures and differences in social information use. Human impacts on marine mammals and their environments are ubiquitous; from chemical and noise pollution, to marine debris, prey depletion and ocean acidification. As a result, no marine mammal populations remain entirely unaffected by human activities. Conservation may be hindered by an inadequate understanding of the behavioral ecology of some of these species. As a result of social structure, social information use, culture and even behavioral syndromes, marine mammal social groups and populations can be behaviorally heterogeneous. As a result responses to conservation initiatives, or exploitation, may be complex to predict. Previous commentators have highlighted the importance of incorporating behavioral data into conservation management and we review these considerations in light of the emerging science in this field for marine mammals. Since behavioral canalization may lead to vulnerability, whereas behavioral plasticity may provide opportunity for resilience, we argue that for many of these socially complex, cognitive species understanding their behavioral ecology, capacity for social learning and individual behavioral variation, may be a central tenant for their successful conservation.